2016
DOI: 10.1002/hed.24541
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral radiotherapy for surgically resected lateralized squamous cell carcinoma of the tonsil

Abstract: Unilateral radiotherapy is an effective and safe treatment option for the postoperative management of lateralized tonsillar cancers, even in patients with N2b disease, and should be recommended in future clinical trial protocols. © 2016 Wiley Periodicals, Inc. Head Neck 39: 17-23, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…However, the majority of patients in the current study who received unilateral RT had N2a to N2b disease (38 of 48 patients; 78%). The findings of the current study are in keeping with the recent report by Rackley et al, who reported the outcomes of a series of 81 patients with lateralized tonsillar cancer and N0 to N2b lymph node disease . With a median follow‐up of 5.7 years, they reported no contralateral disease recurrences and a 5‐year OS rate of 91% and a 5‐year LRC rate of 95%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the majority of patients in the current study who received unilateral RT had N2a to N2b disease (38 of 48 patients; 78%). The findings of the current study are in keeping with the recent report by Rackley et al, who reported the outcomes of a series of 81 patients with lateralized tonsillar cancer and N0 to N2b lymph node disease . With a median follow‐up of 5.7 years, they reported no contralateral disease recurrences and a 5‐year OS rate of 91% and a 5‐year LRC rate of 95%.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the current study are in keeping with the recent report by Rackley et al, who reported the outcomes of a series of 81 patients with lateralized tonsillar cancer and N0 to N2b lymph node disease. 42 With a median follow-up of 5.7 years, they reported no contralateral disease recurrences and a 5-year OS rate of 91% and a 5-year LRC rate of 95%. These outcomes are similar to that of the patients in group 1 in the current study, with a 5-year OS rate of 85% and a 5-year LRC rate of 100%.…”
Section: Discussionmentioning
confidence: 91%
“…We recognise that surgery is only one alternative method for staging the neck and thus avoiding bilateral adjuvant radiotherapy. In fact, a recent series from Rackley et al provides compelling evidence that delivering unilateral adjuvant radiotherapy to surgically resected lateralised tonsillar cancers, even in patients with N2b disease, can be safe and effective without additional surgical staging. We recognise that this would not currently be acceptable in some centres; however, further alternative approaches are also available.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant treatment recommendation for the contralateral neck evolved during the study period. Under our institutional de‐escalation initiatives similar to reports from other recent studies, for tonsil cancer, adjuvant radiation was administered only to the ipsilateral neck for well‐lateralized (>1 cm from the midline) tumors with AJCC 7th edition nodal category of N0‐N2b, thus sparing irradiation of the contralateral neck. For tonsil cancer extending within 1 cm of the midline and/or with AJCC 7th edition N2c‐N3 nodal category, and for base of tongue cancer, irrespective of the distance from the midline or nodal category, the contralateral neck usually received elective neck dissection, and was spared radiation if pathologically negative; adjuvant radiation was administered in the absence of elective neck dissection.…”
Section: Methodsmentioning
confidence: 99%